A formação do professor de português frente aos desafios da práxis: a mobilização de um saber plural - Paiva, Roberta Soares (2009)
It is known that, during Portuguese Language teacher’s academic initial or continued formation, s/he is put in contact with various theoretical bases from Linguistics. However, when it comes to praxis, the teacher’s challenge is evident, because s/he should adapt to praxis demand and also to his/her work conditions the knowledge due to formation in everyday practice. Therefore, we ought to investigate the strategies used in order to promote theory-practice adaptation. Such procedure seldom adopts troubled ways and apparent contradictory behavior in order to get the teacher to establish praxis profile and indeed learn how to teach. As an attempt to reflect about such question, aiming to investigate how teachers proceed knowledge mobilization in Portuguese Language class, we have accomplished a qualitative-interpretative field research, in case study format. Our general objective was to investigate how academic formation aids praxis of a 9thyear- elementary school teacher, who works at a public school from Campina Grande – Paraíba – Brazil. This research is singularly relevant, for it gives voice to one of the most important agents of teaching-learning process – the teacher -, in order to comprehend in a reflexive way the factors that constitute praxis in educational work broader context. This dissertation is mainly based on Applied Linguistics theoretical bases, investigating Portuguese Language teaching crisis, Portuguese Language discipline epistemological and methodological profile and teacher’s formation related to didactic transposition and culminating in a critic look over reflexive teacher concept as a way to respond to nowadays educational demand. In order to do so, among other authors, we are based upon Geraldi et al (1996) to establish a historical scenery of Portuguese Language teaching crisis in Brazil and to consider teachers as a chance factor. We also are based upon Habermas (1983 and 2003) to comprehend how rational-act-related-to-ends regulates the present state of the art in Portuguese Language teaching and also to try to understand the contributions that communicative act may give to such teaching. We are yet based upon Geraldi (1997) and Rafael (2001a and 2001b) in order to analyze not only the plural nature of teacher’s knowledge, but also the knowledge mobilization performed by teachers in practice. As results, we could verify that our informant’s work conditions did influence her praxis. We could also evidence that a satisfactory academic formation had provided a practice that was not able to ignore the present scenery of crisis, which is related to teaching and teachers identity, although it could build a language practice more conscious and pointed towards knowledge conjunct construction.